Identifikasi Faktor Penentu Keberhasilan Pembelajaran Bola Voli Pada Siswa Kelas 5 SDN 4 Batangsaren Kabupaten Tulungagung - Supriyani, Fetri; Harmono, Setyo; Himawanto, Wasis (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
The researcher's observations during instruction and observation at SDN 4 Batangsaren Tulungagung Regency served as the basis for this study. Specifically, several fifth-grade pupils struggled with volleyball. Because of this, kids frequently make mistakes when serving or passing, which makes the match less entertaining to watch. It is well known that service determines the start of the match. The aim of this study is to identify the determining factors for the success of volleyball learning in grade 5 students of SDN 4 Batangsaren Tulungagung Regency. This study employed descriptive quantitative research as its research methodology. Twelve students made up the population, and each one served as a research sample. Methods for gathering data that make use of validity-tested research questionnaires. Tables, diagrams, graphs, pictograms, mean, median, mode, average computations, and standard deviations are used to gain data analysis. The study's findings 1) Internal elements are 73.75% in the high category for the physical category and 63.75% in the high category for the psychological category. 2) External elements are 71.67% in the high category for teachers, 69.27% in the subject matter category, 68.75% in the facilities and infrastructure category, 70.83% in the environment category, and 58.33% in the role of parents category. The study's findings indicate that the internal factor specifically, the physical category, which accounts for 73.75% of the total is the biggest determinant of volleyball learning success.